2018
DOI: 10.22201/fca.24488410e.2018.1849
|View full text |Cite
|
Sign up to set email alerts
|

Institutional ownership, independent board, board size, and firm performance: Evidence from Indonesia

Abstract: This research examines the effect of institutional ownership, independent board and the board size to firm performance. Using fixed effect data panel regression, this research investigates 293 firms listed in the Indonesian Stock Exchange during 2010-2015. Firm performance is proxied by market measure (Tobin's Q). The findings of this research suggest that the institutional ownership, the board of Independence has a positive impact only to Tobin's Q value, while the board size can increase both Tobin's Q. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 42 publications
7
41
2
3
Order By: Relevance
“…Growing companies also had high investment opportunities which could be obtained if they had a project with a positive net present value as a signal to grow in the future. The results of this study are in line with the research conducted by Handriani and Robiyanto (2019), Nason and Wiklund (2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Growing companies also had high investment opportunities which could be obtained if they had a project with a positive net present value as a signal to grow in the future. The results of this study are in line with the research conducted by Handriani and Robiyanto (2019), Nason and Wiklund (2018).…”
Section: Discussionsupporting
confidence: 91%
“…Company size has a positive effect on profitability for large companies tend to have lower profitability and net cash flow volatility (Donelson and Resutek, 2014). The concept of company size is quite widely used to express profitability, which is also supported by empirical studies carried out in developed countries which found a positive relationship (Gaganis, Liu and Pasiouras, 2015;Handriani and Robiyanto, 2019;Sydler, Haefliger and Pruksa, 2014). It was revealed that large companies that use profitability to diversify tend to be able to produce high profitability.…”
Section: Hypothesis Developmentmentioning
confidence: 88%
“…This concept appears to be able to mediate the existed agency problems. CG is defined as a system for directing and controlling a business in operation (Handriani & Robiyanto, 2019;Jaffar, Aziendeh, Shukor, & Rahman, 2018).…”
Section: Literature Review and Hypotheses Stakeholder Theory Agency mentioning
confidence: 99%
“…Agency theory is a concept describing the relationship between principals and agents (Handriani & Robiyanto, 2019). The principal party is the ones that regulate the other party, the agents, to perform all activities on behalf of the principles in their capacity as a decision-maker (Jensen & Meckling, 1976).…”
Section: Agency Theorymentioning
confidence: 99%